Analysis of the Cooling Load of the CC 206 Locomotive Driver's Cab for Determining the Air Conditioning System Capacity - Balla Wahyu Budiarto; Dadang Sanjaya Atmaja; Dimas Adi Perwira (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
The locomotive driver's cabin receives high thermal loads due to solar radiation through the large glass field and heat from the diesel engine room, thus requiring an air conditioning system with the right capacity for the comfort and safety of the operator. This study calculated the cooling load of the CC 206 Locomotive cab and compared it with the installed air conditioning capacity. Calculation using the CLTD/SCL approach heat load method (Hidayat & Restu, 2017; ASHRAE; SNI 03-6572-2001) with data on the structure and material of the casing from the technical data of the facility, at the design conditions of cabin temperature 25.5 °C, outside temperature 32.78 °C, and engine room temperature 40 °C. The conductance value (U) of each element is calculated from the arrangement of the material layers. The results showed a total cooling load of ± 2,585 W (≈ 2,222 kcal/h; ≈ 0.73 TR), dominated by solar radiation through glass and ventilation latent loads. The capacity of the TERMORAIL TRC-8000 installed air conditioner is 8,000 kcal/hour, approximately 3.6 times the calculated load of tune; The margin is functional for pull-downs and extreme conditions. It was concluded that the installed air conditioning unit is very adequate in a tune-like manner, with the potential for optimization in glass shading and compressor capacity regulation.